Type of Track and Trigger system and incidence of in-hospital cardiac arrest: an observational registry-based study - Helen Hogan; Andrew Hutchings; Jerome Wulff; Catherine Carver; Elizabeth Holdsworth; Jerry Nolan; John Welch; David Harrison; Nick Black (BMC, 2020)
Abstract Background Failure to recognise and respond to patient deterioration on hospital wards is a common cause of healthcare-related harm. If patients are not rescued and suffer a cardiac arrest as a result then only around 15% will survive. Track and Trigger systems have been introduced into the NHS to improve both identification and response to such patients. This study examines the association between the type of Track & Trigger System (TTS) (National Early Warning Score (NEWS) versus non-NEWS) and the mode of TTS (paper TTS versus electronic TTS) and incidence of in-hospital ward-based cardiac arrests (IHCA) attended by a resuscitation team. Methods TTS type and mode was retrospectively collected at hospital level from 106 NHS acute hospitals in England between 2009 to 2015 via an organisational survey. Poisson regression and logistic regression models, adjusted for case-mix, temporal trends and seasonality were used to determine the association between TTS and hospital-level ward-based IHCA and survival rates. Results The NEWS was introduced in England in 2012 and by 2015, three-fifths of hospitals had adopted it. One fifth of hospitals had instituted an electronic TTS by 2015. Between 2009 and 2015 the incidence of IHCA fell. Introduction or use of NEWS in a hospital was associated with a reduction of 9.4% in the rate of ward-based IHCA compared to non-NEWS systems (incidence rate ratio 0.906, p < 0.001). The use of an electronic TTS was also associated with a reduction of 9.8% in the rate of IHCA compared with paper-based TTS (incidence rate ratio 0.902, p = 0.009). There was no change in hospital survival. Conclusions The introduction of standardised TTS and electronic TTS have the potential to reduce ward-based IHCA. This is likely to be via a range of mechanisms from early intervention to institution of treatment limits. The lack of association with survival may reflect the complexity of response to triggering of the afferent arm of the rapid response system.